EVALUATION OF QUANTITATIVE AND QUALITATIVE USE OF ANTIBIOTICS IN COMMUNITY HEALTH CENTERS, BOYOLALI DISTRICT, INDONESIA - KARUNIAWATI, HIDAYAH; ANJANI, ROSI HAYYU; UTAMI, KHALIFAH; ISMAIL, WAN ISMAHANISA (International Journal of Applied Pharmaceutics, 2024)
Objective: This study evaluated the quantity and quality of antibiotic use in hospitalized patients and outpatients at the Boyolali District Health Center. Methods: This research is a non-experimental study that collects data by purposive sampling. The inclusion criteria were inpatients and outpatients at the two community health centers in the Boyolali district. Data were analyzed quantitatively using the Anatomical Therapeutic Chemical/Defined Daily Dose (ATC/DDD) method and qualitatively using the Gyssens method. Results: During the study period, 123 hospitalized patients and 338 outpatients met the inclusion and exclusion criteria. The majority of hospitalized patients were women (53.7%) aged 46-65 (30.1%) with a length of stay ≤4 d (56.9%). In comparison, most outpatients were women (61.5%) aged 26-45 (26.9%). The total Defined Daily Dose (DDD)/100 patients-days aged<18 who were hospitalized was 24.3; the most antibiotic was Cefotaxime (36.6%). The total DDD/100 patients days aged ≥ 18 who were hospitalized was 89.7; the most common antibiotic was Thiamphenicol (42.1%). Meanwhile, the most frequently prescribed antibiotic in outpatient was Amoxicillin, 85.3% (age<18 y) and 50.2% (age ≥18 y). Based on Gyssen's analysis, most of the antibiotic administration was in criterion IIIB; namely, the administration of antibiotics was too short. Conclusion: It is necessary to increase the rationality of the use of antibiotics both in inpatients and outpatients.